1975
DOI: 10.1021/j100568a018
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies of ionic solvation. XVI. Lithium-7 and chlorine-35 nuclear magnetic resonance studies in various solvents

Abstract: Publication costs assisted by Michigan State UniversityChemical shifts of lithium-7 nucleus were measured in 11 nonaqueous solvents against 4.0 M aqueous lithium perchlorate solution. Lithium perchlorate, chloride, bromide, iodide, triiodide, and tetraphenylborate were used. The shifts ranged from +2.80 ppm for acetonitrile, down to -2.54 ppm for pyridine. In dimethyl sulfoxide and dimethylformamide no evidence for contact ion pairing was observed. Formation of contact ion pairs was particularly evident in tet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

1979
1979
2009
2009

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(60 citation statements)
references
References 7 publications
5
54
1
Order By: Relevance
“…Variation of parameters such as concentration, counterions and solvent produces changes in the relative proportion and type of environment, which may be reflected by the NMR spectra in terms of chemical shift, line shape and/or line width of the observed resonance. [73] We performed the measurements by keeping the concentration of LiClO 4 constant (0.1 ) and by changing the composition of the H 2 O/CH 3 CN mixtures. The concentration of H 2 O (molar ratio) was increased from 0 to 100 %.…”
Section: Selective Coordination Of LI +mentioning
confidence: 99%
“…Variation of parameters such as concentration, counterions and solvent produces changes in the relative proportion and type of environment, which may be reflected by the NMR spectra in terms of chemical shift, line shape and/or line width of the observed resonance. [73] We performed the measurements by keeping the concentration of LiClO 4 constant (0.1 ) and by changing the composition of the H 2 O/CH 3 CN mixtures. The concentration of H 2 O (molar ratio) was increased from 0 to 100 %.…”
Section: Selective Coordination Of LI +mentioning
confidence: 99%
“…Although the 7 Li chemical shift does not show a linear dependence on the donicity of the pure solvent [13,18,19], the x iso (S) value can be used as a diagnostic criterion of the relative donicity of the two solvents in a binary mixture. In a binary mixture of acetonitrile DMF or DMSO, x iso (S) occurs at very low x(S) values, indicating the preferential solvation of Li by DMF or DMSO.…”
Section: LI Nmr Studiesmentioning
confidence: 99%
“…Solutions of alkalimetal ions, mostly Li + , in DMSO have also been investigated experimentally [46][47][48][49] and theoretically, [41,[50][51][52][53] as well as in water/ DMSO mixtures [54][55][56] and in other solvent combinations. [57][58][59] One of the first reports on the utilisation of 7 Li NMR in the investigation of LiClO 4 in various solvents (including DMSO) was published by Maciel et al [88] In DMSO, no evidence for contact ion pairing was observed [56,60] as might be expected, for instance, in THF (DN = 7.4). [61] It was also shown that Li + interacts preferentially with DMSO electrostatically through the oxygen donor of the S=O group.…”
Section: Introductionmentioning
confidence: 99%